The impact of non-performing loans on banks' lending - Marçal, Tânia Sofia Miranda Martins (2016)
This study analyzes the impact of non-performing loans (NPLs) on credit granted by banks and, consequently, on their management lending policies. An historical review of recent developments in national economies in terms of credit granting and credit quality is presented in this document, along with an analysis of the macroeconomic determinants of NPLs in order to understand the impact of its dynamics in banks’ lending policies and profitability. Furthermore, a perspective of the evolution of regulation on NPLs and the development of the NPLs definition overtime, with the enlargement of the dimensions considered, is also given. Finally, we analyze the measures undertaken by banks to tackle NPLs, in order to evaluate their current situation and the adjustment needed that should be taken regarding the paradigm of banks’ management and the respective business models. Using an unbalanced panel data of quarterly information of 111 banks of the Euro Area, covering the period from 2010 to 2015, and applying a fixed effects model estimated with the Driscoll-Kraay robust approach, we conclude that NPLs show different lagged effects on credit granting. Only after some time of coexistence of simultaneous increase in credit granting and in NPLs, a change in the credit policy occurs. Thus suggesting the existence of rigidity when setting credit policy. Dividing the data into two different groups - countries of Central and Eastern Europe and Peripheral countries (that suffered from financial stress in the period under analysis) – and applying the same approach, we observe significant differences in results between countries.